Nutrition and the cognitive ability of children evidence from Egypt - Cortez, Maria Patricia A. (UMI Company, 1999)
Investing in nutrition is desirable in itself. Adequate nutrition is essential for the proper growth and development of individuals and partly determines the quality of life and well-being of individuals. But there is also an economic rationale for investing in nutrition. Nutrition may have a direct effect on the productivity of labor and an indirect effect through educational achievement. This dissertation focused on the indirect effect of nutrition on labor productivity by examining whether nutritional factors were associated with the cognitive ability of children. The children consisted of toddlers, aged 18-30 months, and schoolers, aged 6-9 years, from a peri-urban Egyptian village. The study found both current nutrition and long-term nutrition to have a significant influence on the cognitive ability of toddlers. For schoolers, only long-term nutrition appeared to have significant influence on their cognitive ability. These results suggest the importance of early nutrition programs for the proper cognitive development of children.--Abstract.